+0  
 
0
253
2
avatar

what adds to -1 but multiplies to -60

Guest Mar 18, 2017

Best Answer 

 #2
avatar+87293 
+5

x + y  = -1      →  y = -1 - x     (1)

x*y   = - 60    (2)

 

Put (1) into (2)

 

x (-1 - x)  = -60

 

-x - x^2  = -60   multiply through by -1  and rearrange

 

x^2 + x - 60   =   0     solving for x   we have

 

 

x =  [ - 1 + sqrt(241)] / 2    and y   =  [ - 1 - sqrt(241)] / 2        or

 

x = [ - 1 - sqrt(241)] / 2     and  y  =  [ - 1 + sqrt(241)] / 2

 

 

cool cool cool

CPhill  Mar 18, 2017
 #1
avatar+7153 
+6

Technically, the two numbers are:

\(\frac{-1+\sqrt{241}}{2} \text{ . . .and. . . } \frac{-1-\sqrt{241}}{2}\)

 

I found just it by using the quadratic formula on this equation:

x2 - x - 60 = 0

 

There are no integers that add to -1 but multiply to -60.

 

Does your problem look like this:

x2 - x - 60 = 0

 

Or is there a number in front of the x2  ?

hectictar  Mar 18, 2017
edited by hectictar  Mar 18, 2017
 #2
avatar+87293 
+5
Best Answer

x + y  = -1      →  y = -1 - x     (1)

x*y   = - 60    (2)

 

Put (1) into (2)

 

x (-1 - x)  = -60

 

-x - x^2  = -60   multiply through by -1  and rearrange

 

x^2 + x - 60   =   0     solving for x   we have

 

 

x =  [ - 1 + sqrt(241)] / 2    and y   =  [ - 1 - sqrt(241)] / 2        or

 

x = [ - 1 - sqrt(241)] / 2     and  y  =  [ - 1 + sqrt(241)] / 2

 

 

cool cool cool

CPhill  Mar 18, 2017

7 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.